Fear of Uncertainty Makes You More Anxious? Effect of Intolerance of Uncertainty on College Students’ Social Anxiety: A Moderated Mediation Model - Li, Jie; Xia, Ying; Cheng, Xinying; Li, Shijia (Frontiers in Psychology, 2020)
Purpose: This study investigated the relationships among intolerance of uncertainty (IU), social anxiety (SA), rumination, and pessimistic explanatory style (PES) in a sample of college students. Methods: Questionnaires were completed by 533 college students. Results: Rumination partially mediated the relationship between IU and SA, and PES plays an important role in moderating the direct path (IU→SA) and the first part of the mediation process. When the PES is low, IU predicts SA less strongly but is related to rumination. Conversely, IU in individuals with a high PES predicts SA more directly. Conclusion: Rumination plays a mediating role between IU and SA, and the PES moderates the direct path and the first stage of the mediation model.